OC-040 Community-based Endoscopy In A Car Park. Fantasy Or Reality?. (9th June 2014) - Hitchen, A; Kompo, B; Phillips, P; Price, E; Deans, G; Ahluwalia, NK
Abstract : Introduction: Owing to safety and quality concerns raised by BSG in 1990s, Community Based Endoscopy (CBE) rapidly declined. In 2014 CBE is back on the agenda with CCGs demanding a safe, high-quality, sub-tariff, 7 day endoscopy service close to the patient's home, at a time of the patient's choosing. We describe 5 years experience of a fully JAG accredited consultant-delivered completely mobile endoscopy service provided in shopping centre car parks throughout Greater Manchester (GM). Methods: In 2007, concept emerged out of a tender from 10 PCTs demanding safe and high quality endoscopy in the community. A linked-3-trailer unit with spacious waiting area for patients/relatives, consent-counselling, preparation, examination, decontamination and recovery areas. with its own – water, electricity, waste disposal, e-communications and administration network was commissioned with integral office, staff kitchen/rest room and changing area. All staff undergo rigorous mandatory induction and regular updates, CPD, audits as per JAG. Emergency scenarios are regularly rehearsed and audited. Full complement of ALS certified staff support consultants 8 am–8 pm, 7/7 [360] days in diagnostic UGI and LGI endoscopies [including polypectomies] and deliver 36 units/day. All patients undergo JAG-standard monitoring of pulse, BP, O2 saturation, sedation and pain scores. All records are paperless, live and e-MAXIM andUNISOFT-based. All patients are contacted within 24 h by an experienced nurse to record any untoward incident. Patient and family feedback and regular meetings with GP allows total quality management in service delivery. Though no age limit, patients with IDDM, BMI >40, >25st and ASA≥3+ are excluded. Quarterly audits are shared with commissioners. Unit relocates biweekly to 7 convenient locations with adjacent free parking. Results: Of 26599 (10539 UGI, 10583 Flexi-Sig, 5477 Colonoscopy) procedures, 1 in 3 patients opted for out-of-hours or weekend as first choice. LGI- 93% good-bowel prep, 91% caecal intubation, 8.8% adenoma detection, 97% polyp recovery and 100% Bx for diarrhoea. UGI- 98% D2 intubation, 100% 6 week repeat for GU, 84% unsedated. Biannual JAG-GRS compliant audits showed 0% 30 day mortality, 0% UGI SAE and 5 (0.018%) unplanned hospital admissions 4 requiring surgery due to colon perforation [one post-flexi detected in the unit (diverticular disease), 1 from polypectomy, 2 diagnostic colonoscopy] and fifth due to hyponatremia (CitraFleet – now discontinued) requiring electrolyte correction. Conclusion: CBE is ready for prime time, just at the right time, as commissioners are now seeking more care in the community wherever safely possible. We however, recommend caution as model for sub-tariff CBE endoscopy from static sites needs to be first piloted. Disclosure of Interest: None Declared.